Modelling to evaluate the water resource implications of planned infrastructure development in the Lake Tana sub-basin, Ethiopia - Alemayehu, Tadesse; McCartney, Matthew P.; Kebede, S. (2009)
Lake Tana is important for domestic water supply, hydropower, fisheries, grazing and water for livestock, as well as reeds for boat construction. It is also important for water transport and as a tourist destination. Currently, the water resources of the catchment are largely untapped. However, water resource development is being encouraged to stimulate economic growth and reduce poverty. In this study, the Water Evaluation And Planning (WEAP) model was used to determine the water availability for different irrigation and hydropower schemes proposed. Three development scenarios were simulated and the likely impact of future water resource development on lake water levels was assessed. For each scenario, the model was used to simulate water demand in three sectors (i.e. irrigation, hydropower and downstream environmental flows) over a 36-year period of varying flow and rainfall. The simulation results revealed that if all the planned development occurs on average 2,198 GWhy-1 power could be generated and 677 Mm3y-1 of water supplied to irrigation schemes. However, the mean annual water level of the lake would be lowered by 0.44 meters with a consequent decrease in the average surface area of the lake of 30 km2. As well as adverse ecological impacts this would have significant implications for shipping and the livelihoods of many local people.